Finance for integrated landscape management: A landscape approach to climate-smart cocoa in the Juabeso-Bia Landscape, Ghana - Lawrence, D.; Louman, B. (Tropenbos International, 2021)
This case study looks at how an international agribusiness, the source of the flow, strengthens the capacity of its smallholder providers to generate more income from their cocoa production and become more climate resilient. The case study focuses on how the company integrates technical support to producers with strengthening their capacity to save and invest through village savings and loan associations (VSLAs) in Ghana.